2020
DOI: 10.3390/atmos11020152
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Green Infrastructure in Residential Development—A Consumer Perspective

Abstract: This paper investigates the literature and theoretical underpinning of the concept of "willingness to pay" (WTP) for green infrastructure (GI) with consequences for residential development. The benefits of GI in urban settlements include improved air quality, attenuation of the urban heat island, thermal insulation and lower energy bills for green roofs and walls, the creation of social amenity space, a habitat for biodiversity, and stormwater water attenuation. Collectively, these benefits are termed eco-syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 115 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…The interest to purchase a dwelling increased with the level of greenery in the courtyard. Considering that interest and attractiveness matter significantly in the buyer's psychological cost-benefit analysis, it can be concluded that green spaces may influence willingness to pay price for a dwelling [32]. If the greenness of the courtyard increases attractivity and interest of a buyer, the apartment attracts a greater number of potential buyers (bidders).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest to purchase a dwelling increased with the level of greenery in the courtyard. Considering that interest and attractiveness matter significantly in the buyer's psychological cost-benefit analysis, it can be concluded that green spaces may influence willingness to pay price for a dwelling [32]. If the greenness of the courtyard increases attractivity and interest of a buyer, the apartment attracts a greater number of potential buyers (bidders).…”
Section: Discussionmentioning
confidence: 99%
“…Buyers' present and future needs and preferences are fundamental in purchase evaluation and psychological cost-benefit analysis, therefore priority and significance that green space have for individual and positioning among those needs will play role in output of customer evaluation [32].…”
Section: Green Space In Housing Developmentmentioning
confidence: 99%
“…-enhances the role and importance of blue infrastructures in green infrastructure planning. ■ Applicability [45] -must be considered in addition to adaptability and implementation, -being realistic, is the guarantee of its implementation and development. ■ Governance [40], [41], [46] -a collaboration between the government actors and the citizens in the planning processes as a guarantee for project success.…”
Section: Urban Green Infrastructure Model (Ugim) For Children-nature ...mentioning
confidence: 99%
“…We assume in the construction of the indicator system that GDP and GDP per capita represent the stage of regional economic development [96,97], fiscal balance and loans reflect the potential and strength of government support for housing market development [98], population and urbanization represent the potential scale of housing demand [99], residents' income and consumption level reflect the ability and willingness to consume housing, the secondary industry represents the real economy [100], the tertiary industry and finance reflect the support capacity of intermediary services, import and export represent the development level of the open economy [101], health facilities and public transport conditions reflect the capacity and quality of infrastructure services [102], and the green land area and the number of parks reflect the quality of the ecological environment [103]. The analysis of independent and dependent variables based on the Geodetector method helps reveal the connections between the spatial inequality in the housing market and the stage of economic development, government support or policy orientation, urbanization, industrialization, globalization, infrastructure and public services, and environmental quality, and it provides the basis for policy design.…”
Section: Index Selectionmentioning
confidence: 99%